Electrical and dielectric properties of sprayed tungsten oxide thin films - M.M. Althubayti; Ali Abdel-Daiem; Moustapha Farghal; Aicha Loucif; Mohammed Salah Aida (Next Materials)
In the present work, the electrical and dielectric properties of tungsten-oxide thin films have been investigated. The tungsten-oxide films were prepared using the spray pyrolysis technique using ammonium par paratungstate salt. The films were prepared with various substrate temperatures. The dielectric measurements were carried out using impedance spectroscopy measurements in the frequency range of 100 Hz ∼ 1 MHz at ambient temperature. The dielectric characterization was based on the measurement of the ac conductivity (σac), capacity, the real part of the dielectric constant (ε′), imaginary part or dielectric loss (ε″), and the loss factor (tan δ) as functions of the electrical frequency. The DC conductivity was thermally activated and was found to exhibit an Arrhenius variation. The polarization at low frequency was ascribed to the interfacial polarization at the grain boundaries, while at high frequency it was associated with ionic polarization. The frequency dependence of σac(ω) obeys the power law ωs, with the exponent s being less than unity (in order of 0.64). This AC conduction was interpreted in terms of the correlated barrier hopping (CBH) model. The variation of dielectric loss ε” was used to estimate the barrier height Wm of the hopping conduction between charge defect states and the conduction band.